Posted by **phyllys** on Sunday, January 6, 2013 at 5:56pm.

f(x)=x^3-3x^2+x-12

=x^2(x-3)+4(x-3)

=x^2+4) (x-3)

so if f(x) = 0 at x = 3,+/- 2i.

what is the f(x) factored form

- Pre-Cal. -
**Damon**, Sunday, January 6, 2013 at 6:04pm
(x)=x^3-3x^2+x-12

=x^2(x-3)+4(x-3) Not true

That would be

x^3 - 3x^2 + 4x - 12

=========================

You have told me that the zeros of the function are:

3

2i

-2i

Therefore the factored form is:

(x-3)(x-2i)(x+2i)

try multiplying that out

- Pre-Cal. -
**Damon**, Sunday, January 6, 2013 at 6:09pm
that is

(x^2+4)(x-3)

which is

x^3 - 3 x^2 + 4x -12

so I think you have a typo in your opening line

- Pre-Cal. -
**phyllys**, Monday, January 7, 2013 at 7:48pm
where is the typo in which opening line? And I believe I used the wrong symbol for the factored function it's suppose to be a plus sign over a __ but I can't figure how to type this. and maybe that's what is giving us the answer you have given me. Could that be it? and that is not -12, negative 12 it's minus 12

## Answer this Question

## Related Questions

- Pre-Cal. - write f(x) in factored form.
- Pre-Cal. - use the complex zeros to give fully factored form, the first factor ...
- Pre-cal (please help) - A polynomial of degree 4 that increases the y-axis at 6 ...
- pre-calculus - find the complex zeros of the polynomial function. write F in the...
- alegebra - 1. What is the factored form of 4x 2 + 12x + 5? (1 point) (2x + 4)(2x...
- Math - Can someone please tell me Why is (4x + 5) (2x - 1) + (x - 9) (2x - 1) ...
- Math - Can someone please tell me Why is (4x + 5) (2x - 1) + (x - 9) (2x - 1) ...
- Algebra - F) Why is (3x + 5) (x - 2) + (2x - 3) (x - 2) not in factored form? ...
- Mat 117 - •I am having trouble figuring out this question. Why is (3x + 5) (x - ...
- Integrated Math 1 - Consider y=x^2+8x+16. What is the correct way to factor this...